Genotyping of staphylococcus aureus isolated from dairy herds in México - Castañeda Vázquez, Hugo; J í¤ger, Sybille; Wolter, Wilfried; Zsch í¶ck, Michael; Castañeda Vazquez, Martha Alicia; El Sayed, Amr (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
In the present work, Staphyloccous aureus field strains were isolated from 27 mastitic cows representing 12 dairy herds. This was selected of almost 3,000 field strains of mastitic cows. The strains were subjected to different Polymerase Chain Reaction (PCR) to detect the toxin encoding genes SEA, SEB, SEC, SED, SEE, SEG, SEJ and TST genes. The investigated strains were then subjected to fingerprinting by the means of Pulse Field Gel Electrophoresis (PFGE). The screening for the previously mentioned toxin encoding genes revealed the absence of all toxin encoding genes with the exception of SEI which could be detected in a single strain. Meanwhile, the data obtained through the PFGE analysis indicated the close relationship of S. aureus field strains responsible for the induction of mastitis in western Mexico.